Towards a Christian ethic of work in South Africa - L. Kretzschmar (Acta Theologica)
This paper draws on the academic field of Christian ethics and focuses attention on an ethic of work within the South African context. Key terms such as ‘an ethic of work’, ‘a work ethic’ and ‘ethics at work’ are discussed in relation to varied experiences of work. The issues of why one ought to work and what constitutes ‘good’ work are discussed with reference to current ethical and economic challenges. I argue that a Christian worldview, or understanding of reality, provides a much more credible contribution to an ethic of work than either a materialist view of reality or a system of patronage.